2022
DOI: 10.3389/fpubh.2022.996885
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of maternal near-miss among women admitted to public hospitals in North Shewa Zone, Ethiopia: A case-control study

Abstract: BackgroundA maternal near-miss (MNM) refers to a woman who presents with life-threatening complications during pregnancy, childbirth, or within 42 days of termination of pregnancy but survived by chance or due to the standard care she received. It is recognized as a valuable indicator to examine the quality of obstetrics care as it follows similar predictors with maternal death. Ethiopia is one of the sub-Saharan African countries with the highest rate of maternal mortality and morbidity. Thus, studying the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The current study showed that the leading causes of MNM were pregnancy induced hypertension and severe postpartum hemorrhage, which are comparable to the ndings of studies conducted elsewhere in Ethiopia (14,15,(21)(22)(23)(24) and other African countries (17,18). Pregnancy related infection (sepsis) was associated with the highest case fatality which is similar with the ndings of earlier studies done in other parts of the country (23,25) and other developing countries (17,18).…”
Section: Underlying and Contributory Causessupporting
confidence: 89%
See 1 more Smart Citation
“…The current study showed that the leading causes of MNM were pregnancy induced hypertension and severe postpartum hemorrhage, which are comparable to the ndings of studies conducted elsewhere in Ethiopia (14,15,(21)(22)(23)(24) and other African countries (17,18). Pregnancy related infection (sepsis) was associated with the highest case fatality which is similar with the ndings of earlier studies done in other parts of the country (23,25) and other developing countries (17,18).…”
Section: Underlying and Contributory Causessupporting
confidence: 89%
“…According to a recent systematic review and meta-analysis study, the global prevalence of maternal near miss was 1.4% (11). Among the studies that have been conducted in Africa, the weighted pooled prevalence of MNM was 31.9 per 1000 live births, with signi cant heterogeneity between studies (6).…”
Section: Introductionmentioning
confidence: 99%
“…It found that there were nine maternal deaths, a 4.4% case fatality rate, and 151 perinatal mortality rates per 1,000 live births ( 34 ). Additionally, it was found that referral systems greatly increase the risk of maternal death in Ethiopia ( 35 , 36 ). Most of the referred cases might have potentially complicated cases involving the central nervous system, coma or loss of consciousness lasting 12 h or more; metabolic coma (consciousness loss and urine containing ketoacids and glucose); stroke, status epilepticus, involuntary convulsions, or complete paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 According to a recent systematic review and meta-analysis study, the global prevalence of MNM was 1.4%. 8 Among the studies that have been conducted in Africa, the weighted pooled prevalence of MNM was 31.9 with significant heterogeneity between studies. 6 Near miss events are common and are estimated to be around 12 times more frequent than maternal deaths.…”
Section: Introductionmentioning
confidence: 99%
“…6 Near miss events are common and are estimated to be around 12 times more frequent than maternal deaths. [8][9][10][11] Studies have shown that predictors of maternal near misses are postpartum hemorrhage, pregnancy induced hypertension, sepsis, ruptured uterus, and abortion. 1,4,12 Improving maternal health remains an important topic of sustainable development goals (SDG), which is to reduce the global Maternal Mortality Ratio (MMR) to less than70 per 100,000 live births by 2030 and Ethiopia also intends to achieve this target by 2030.…”
Section: Introductionmentioning
confidence: 99%